Challenges in Interventional Radiology: The Pregnant Patient - Moon, Eunice K.; Wang, Weiping; Newman, James S.; Bayona-Molano, Maria Del Pilar (Seminars in Interventional Radiology, 2013)
A pregnant patient presenting to interventional radiology (IR) has a different set of needs from any other patient requiring a procedure. Often, the patient's care can be in direct conflict with the growth and development of the fetus, whether it be optimal fluoroscopic imaging, adequate sedation of the mother, or the timing of the needed procedure. Despite the additional risks and complexities associated with pregnancy, IR procedures can be performed safely for the pregnant patient with knowledge of the special and general needs of the pregnant patient, use of acceptable medications and procedures likely to be encountered during pregnancy, in addition to strategies to protect the patient and her fetus from the hazards of radiation.
Keywords: pregnancy; interventional radiology; medication; radiation safety